Impresión 3D para planificación de abordaje neuroquirúrgico - Experiencia en el Nordeste Argentino - Rodriguez Gacio, Nicolás; Maidana, Florencia Antonella; Ruiz Moreno, Camila; Ramirez Maisuls, Carlos; Rodriguez Cuimbra, Silvia; Olivetti, Martin (Revista Argentina de Neurocirugía, 2021)
Introduction: Effective surgical training and careful preoperative planning are important for success in neurosurgical procedures. As a 3D printed skull base lesion model shows the specific spatial arrangement of a tumor, and its anatomical relations, we believe it could play an important role in surgical planning.Objectives: Emulate the practice of 3D Printing in our environment and analyze its usefulness for surgical planning.Case presentation: 41-year-old female patient who attends the consultation for endocrine, visual field disorders and headache. On examination, the patient was lucid, with hypo reactive intermediate pupils, bitemporal hemianopia, mobilizing 4 extremities without deficit. In MRI of the brain, a selar-suprasellar space-occupying lesion with a multilobed appearance is observed, which invades the interpeduncular cistern and displaces structures of the third ventricle.Intervention: The patient underwent resective surgery through a subfrontal approach, achieving complete macroscopic resection. Evolving later with GOS 5Conclusion: 3D printing models provide to us important of perspectives for the approach to the lesion and constitute an important low-cost tool for neurosurgeons in training. We highlight the importance of interdisciplinarity for the arrival of favorable results.
Keywords: approach; 3D printing; skull base; tumor